Can backward sled towing potentiate sprint performance? - Monaghan, D. J.; Cochrane, D. J. (The Journal of Strength and Conditioning Research, 2020)
The objectives of this study were to determine whether backward sled towing can elicit a postactivation potentiation response to enhance forward 5-m sprint performance and to determine whether sled loading through a reduction in velocity can elicit an improvement in 5-m sprint performance. A randomized design was used to examine the effects of forward and backward sled tow loading of 35 and 55% reduction of individual's maximal velocity (rVelmean) on 5-m sprint performance. Eighteen well-trained male subjects performed 4 intervention sessions (55% rVelmean backward; 55% rVelmean forward; 35% rVelmean backward; and 35% rVelmean forward) separated by a minimum of 24 hours. Intervention sessions included baseline unresisted 5-m sprints, followed by 3 loaded sled tows over a distance of 3.2 m or 5 m for heavy and light loads, respectively. An unresisted 5-m sprint was completed after 6 and 12 minutes of rest. Mean sprint velocity, electromyography, sprint kinematic, and temporal data were collected during each session. Sled towing, irrespective of load or rest period, produced no significant change in 5-m sprint velocity (p > 0.05). In addition, there were no significant changes in electromyography, kinetic, and temporal data; however, current findings support previous research of confirming muscle activation and vertical force production during sprint acceleration. It is unclear whether individualizing a reduction in velocity is a superior method to percent body mass for optimizing sled loading in well-trained male subjects.